Discussion on the Regulatory Test of Artificial Intelligence-Enabled Medical Devices and Their Technical Potential in Tumor Immunity - Han, Le; Chen, Yuzhe; Wang, Lifeng; Zong, Xin (Trends in Immunotherapy, 2025)
The deep integration of AI and immunotherapy is reshaping the paradigm of cancer diagnosis and treatment. From biomarker discovery to personalised treatment, from adverse reaction warnings to empowering grassroots communities, despite bottlenecks such as data silos, algorithm transparency, and ethical controversies, the technical potential of AI has already begun to emerge. This paper examines the evolution of global AI medical device policies and product release trends over the past decade, identifying the issues and challenges posed by the current regulatory landscape, including: first, the structural imbalance between the regulatory system and the rate of technological innovation; second, the double-standardisation dilemma between risk classification and clinical validation; and third, the ethical paradox of data governance and algorithmic transparency. The challenges faced include: first, Technology Fusion: AI at the Crossroads with Synthetic Biology and Nanotechnology. Second, Algorithm Transparency and Ethical Paradox. Third, In-Depth Application of Regulatory Technology. Fourth, Collaborative Innovation in Industrial Ecology. Based on this, this paper provides systematic recommendations for addressing the regulation of AI medical devices: first, Building a Dynamic Adaptive Technology Supervision System. Second, Perfecting the Full Life Cycle Clinical Evidence Chain. Third, Create an Open and Collaborative Industrial Innovation Ecosystem. Fourth, Deepen International Regulatory Coordination and Cooperation. Recommendations for the regulation of AI medical devices in the field of immunotherapy: First, Multi-Modality Imaging and Treatment Integrated Platform. Second, Intelligent Empowerment of Primary Care. Third, Global Collaboration and Data Sharing.